2022
DOI: 10.1073/pnas.2112870119
|View full text |Cite
|
Sign up to set email alerts
|

ER-resident STIM1/2 couples Ca 2+ entry by NMDA receptors to pannexin-1 activation

Abstract: Pannexin-1 (Panx1) is a large-pore ion and solute permeable channel highly expressed in the nervous system, where it subserves diverse processes, including neurite outgrowth, dendritic spine formation, and N-methyl D-aspartate (NMDA) receptor (NMDAR)-dependent plasticity. Moreover, Panx1 dysregulation contributes to neurological disorders, including neuropathic pain, epilepsy, and excitotoxicity. Despite progress in understanding physiological and pathological functions of Panx1, the mechanisms that regulate i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 64 publications
2
8
0
Order By: Relevance
“…S6D1 and Video1) revealed that as much as 80-90% of the STIM1-decorated ROI overlapped with the DGKε-Myc- decorated ROI (Table 1, M1) and 50-60% of DGKε-Myc-positive ROI colocalized with STIM1-positive ROI (Table 1, M2). STIM1 was concentrated in the perinuclear region resembling the pattern observed earlier in resting HEK293 cells (52). DGKε-Myc and STIM1 colocalized to a high extent in this perinuclear part of the endoplasmic reticulum while they tended to be separated toward the cell periphery (Fig.…”
Section: Resultssupporting
confidence: 80%
“…S6D1 and Video1) revealed that as much as 80-90% of the STIM1-decorated ROI overlapped with the DGKε-Myc- decorated ROI (Table 1, M1) and 50-60% of DGKε-Myc-positive ROI colocalized with STIM1-positive ROI (Table 1, M2). STIM1 was concentrated in the perinuclear region resembling the pattern observed earlier in resting HEK293 cells (52). DGKε-Myc and STIM1 colocalized to a high extent in this perinuclear part of the endoplasmic reticulum while they tended to be separated toward the cell periphery (Fig.…”
Section: Resultssupporting
confidence: 80%
“…It's possible that additional proteins are involved to relay the signaling output to PANX1. For example, the endoplasmic reticulum (ER)-resident stromal interaction molecules (STIM1/2) have recently been noted to mediate events between NMDAR and PANX1 (40). Future studies are required to fully decipher the underlying mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…Panx1 channels are expressed in neurons and glial cells, including microglia cells and astrocytes, as well as in the neurovascular unit [17][18][19][20] . Panx1 channels play critical roles in cell death [21][22][23][24][25] , calcium signaling 26,27 , neurotoxicity regulation 28,29 , non-synaptic communication 30,31 , inflammation 22,32,33 , neuronal excitability 34 and endema 35 . The relevance of Panx1's interaction with the cytoskeleton and whether this interaction contributes to cytoskeletal abnormalities in NDDs remains to be explored 36,37 .…”
Section: Introductionmentioning
confidence: 99%